Philosophical Perspectives on Galen of Pergamum: Four Case-Studies on Human Nature and the Relation between Body and Soul - Vinkesteijn, Robert (Philosophia Antiqua, 2022)
An innovative study of the work of Galen, and the topics of body-soul relations, human nature and melancholy in ancient Greek philosophy.